Evidence-based practice at Patan Academy of Health Sciences, Nepal: knowledge, attitude, behavior and barriers (Journal of Patan Academy of Health Sciences, 2018)
Introduction: Evidence based practice (EBP) is the use of current best evidence in making decisions about the care of individual patients. The aim of this study was to explore the practices, attitudes, knowledge and perceived barriers in relation to EBP among faculty members at Patan Academy of Health Sciences (PAHS), Nepal. Methods: This was a cross-sectional survey study. Participants were faculty members (both clinical and non-clinical) at PAHS. The main outcomes were attitude towards the usefulness of EBP, the frequency of use of EBP in practice, and the barriers to carrying out EBP. Results: One hundred and seventy-two faculty members participated in this survey. Ninety five percent knew it was used for clinical decision making and the majority used it for teaching. Senior faculty spent more time on searching for evidence and reading compared to junior faculty. There was no difference between clinical and non-clinical departments. The main barriers to EBP were inadequate teaching learning support by 49% (85/172) followed by inadequate time 30% (52/172). Conclusions: The study showed that faculty at PAHS had a generally positive attitude towards EBP. EBP could be better facilitated by proper teaching and allocation of dedicated time.